WASAKA Concept Implementation in Islamic Education towards Banjar Society of South Kalimantan in 4.0 Era - Syaifullah, A.; Surawardi, Surawardi (Khalifa Journal of Islamic Education, 2020)
This paper is aimed to analyze WASAKA concept as Banjar society, Islamic education and how to implement it in Banjar society in 4.0 era. WASAKA (Waja Sampai Kaputing) is pronounced by Antasari Prince, national hero from South Kalimantan, and be the society character in South Kalimantan The character values are religious, tough, honest, intelligent and caring .These values can be relevant and synergize with Islamic education in Banjar society in 4.0 era due to education character in 4.0 era receives a lot of challenges from outside. Nowadays, foreign character and culture from outside intrude without filtering process so it can influence and be character degradation of our education. Therefore, it is important to understand deeply and comprehensively how innovation based Islamic education and WASAKA character implementation in 4.0 character education. Then, WASAKA character values in character education in the 4.0 era will be assessed using the literature study methodology and relevant literature materials as the sources. The results is WASAKA concept in Islamic education in Banjar society of South Kalimantan is as reinforcement of character education in the 4.0 era. In sum, WASAKA concept implementation in Banjar society in 4.0 era can be solutions to face character degradation in 4.0 era.